Paleoecology of an Early Holocene Wetland on the Canadian Prairies - Boyd, Matthew (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2003)
AbstractA plant macrofossil record from the glacial Lake Hind basin is used to reconstruct early postglacial wetland plant succession and paleohydrology. Between >10.6 and 9.1 ka BP, there are four plant assemblage zones: (1) an early (>10.6 ka BP) zone dominated by Cyperaceae and aquatics; (2) a subsequent zone (~10.6-10.1 ka BP) with emergents (Menyanthes trifoliata, Potentilla palustris, Scirpus validus) and fewer aquatic plants; (3) an interval between ~10.1 and 9.8 ka BP dominated by Drepanocladus aduncus; and (4) a zone between ~9.8 and 9.1 ka BP with Menyanthes trifoliata and Equisetum. These data indicate a gradual decline in water depth between 10.6 and 10.1 ka BP due to deepening of one or more outlets of glacial Lake Hind. From ~10.6 to 9.1 ka BP, the importance of Menyanthes records pronounced, seasonal, flooding. Furthermore, lack of evidence for complete drawdown and terrestrialization in the basin – despite local and regional evidence for postglacial warming – indicates that this wetland was minimally impacted by climate change up to at least 9.1 ka BP. Persistence of very wet conditions locally is consistent with recent results from south-central Saskatchewan, and may be due to release of meltwater from stagnant ice. However, frequent low-energy flooding of the basin by the Souris River is more plausible. In general, the apparent insensitivity of aquatic habitats to abrupt climate change in some locales on the Canadian Prairies demonstrates the potential long-term mitigating effects of local hydrological factors.